2017
DOI: 10.48550/arxiv.1701.08499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rest frames and relativistic effects on de Sitter spacetimes

Ion I. Cotaescu

Abstract: It is shown that the Nachtmann boosting method of introducing coordinates on de Siter manifolds can be completed with suitable gauge transformations able to keep under control the transformation under isometries of the conserved quantities. With this method, the rest local charts (or natural frames) are defined pointing out the role of the conserved quantities in investigating the relative geodesic motion. The advantages of this approach can be seen from the applications presented here. For the first time, the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 13 publications
(32 reference statements)
1
34
0
Order By: Relevance
“…In Ref. [10] we have shown that we can define the rest frame {t , x } of the mobile m as the local chart in which this stays at rest in the origin x = 0. This means that for an observer O , comoving with the rest frame, the mobile m has the momentum P = 0.…”
Section: Relative Geodesic Motionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Ref. [10] we have shown that we can define the rest frame {t , x } of the mobile m as the local chart in which this stays at rest in the origin x = 0. This means that for an observer O , comoving with the rest frame, the mobile m has the momentum P = 0.…”
Section: Relative Geodesic Motionmentioning
confidence: 99%
“…A particular case studied in Ref. [10] is when the measurement is performed in the origin of the mobile frame, M ≡ O (with ξ = 0 and κ = κ(t * )). that hold only for small time intervals such that ωδt 1.…”
Section: Relativistic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…All these spacetimes have highest possible isometries [1] representing thus a good framework for studying the role of the conserved quantities with physical meaning [2,3,4] in studying the relative geodesic motion. With their help we constructed recently the dS relativity [5] in comoving charts [6] and the AdS relativity [7] in central charts (i. e. static and spherically symmetric) that complete our image about the special relativity in spacetimes with maximal symmetry.…”
Section: Introductionmentioning
confidence: 99%